A detailed paleomagnetic and rock-magnetic investigation of the Matuyama-Brunhes geomagnetic reversal recorded in the tephra-paleosol sequence of Tlaxcala (Central Mexico) - Soler-Arechalde, Ana M.; Goguitchaichvili, Avto; Carrancho, Ángel; Sedov, Sergey; Caballero-Miranda, Cecilia I.; Ortega, Beatriz; Solis, Berenice; Contreras, Juan J. Morales; Urrutia-Fucugauchi, Jaime; Bautista, Francisco (Frontiers in Earth Science, 2015)
Geomagnetic reversals are global phenomena that require several stratigraphic correlation and dating methods for their firm identifications. For about 50 years the paleomagnetists attempted to acquire as many detailed records as possible using the magnetic memory of sediments and lava flows. Yet, transitional field behavior remains poorly characterized largely because of sporadic aspect of volcanic eruptions. In some specific cases, paleosols such as those developed from alluvial or aeolian sediments, may also record the variations of the Earth's Magnetic Field across the polarity changes. Here, we report a detailed paleomagnetic and rock-magnetic investigation on some radiometrically dated chromic Luvisols located in Central Mexico carrying detrital or chemical remanent magnetization. The research was developed in order (i) to demonstrate the primary origin of the recorded magnetic remanence and (ii) to show that paleosols are good candidates to provide a high resolution record of the behavior of Earth magnetic field during geomagnetic reversals. The lower part of the paleosol sequence shows a clearly defined reverse polarity magnetization followed by geomagnetically unstable transitional field and ended by normal polarity remanence. Considering the K-Ar datings available at the bottom of the sequence, observed polarity changes most probably correspond to the Matuyama-Brunhes transition. Our AMS and rock magnetic data suggest that the magnetization is acquired during the initial stage of soil formation in context of active volcanic activity since the magnetic fabric is essentially sedimentary and reverse and normal polarity paleodirections are almost antipodal. Moreover, titanomagnetites are identified as main magnetic carriers of rock-magnetic measurements including thermomagnetics and hysteresis cycles. We propose that the transition recorded in this study correspond to the Brunhes-Matuyama boundary andabstractthat the chromic Luvisols are potentially good recorders of the paleosecular variation. The identification of the Brunhes-Matuyama boundary within the studied sequence has fundamental significance for improving the chronological scale of Tlaxcala paleosol-sedimentary sequence and its correlation with the global proxies.